2008
DOI: 10.1187/cbe.07-07-0050
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Influence of Field- and GIS-based Inquiry on Student Attitude and Conceptual Knowledge in an Undergraduate Ecology Lab

Abstract: Combining field experience with use of information technology has the potential to create a problem-based learning environment that engages learners in authentic scientific inquiry. This study, conducted over a 2-yr period, determined differences in attitudes and conceptual knowledge between students in a field lab and students with combined field and geographic information systems (GIS) experience. All students used radio-telemetry equipment to locate fox squirrels, while one group of students was provided an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 35 publications
0
24
0
1
Order By: Relevance
“…Although student learning gains were significant at multiple institutions that vary substantially in student demographics, within an institution learning gains were not significant in all semesters. Similarly, Simmons et al (2008) found that students involved in an inquiry-based field study of habitat use by fox squirrels (Sciurus niger) showed a significant positive increase in student attitudes in one year but not the other. Furthermore, learning gains in students' knowledge related to habitat features, spatial attributes, and population sampling techniques varied among the three concepts and between years.…”
Section: Introductionmentioning
confidence: 99%
“…Although student learning gains were significant at multiple institutions that vary substantially in student demographics, within an institution learning gains were not significant in all semesters. Similarly, Simmons et al (2008) found that students involved in an inquiry-based field study of habitat use by fox squirrels (Sciurus niger) showed a significant positive increase in student attitudes in one year but not the other. Furthermore, learning gains in students' knowledge related to habitat features, spatial attributes, and population sampling techniques varied among the three concepts and between years.…”
Section: Introductionmentioning
confidence: 99%
“…The case for the wider use of GIS (beyond the designated module) is also supported by Simmons et al (2008) who showed that using GIS in ecology improved both students' theoretical understanding and their practical knowledge of ecology. Similarly, Lo et al (2009) found that by creating a GIS map in historical geography students improved their historical and spatial thinking skills.…”
Section: Assessmentmentioning
confidence: 94%
“…The linking of GIS and field teaching nicely illustrates the potential for both "teaching about GIS" (as in GIS modules) and also "teaching with GIS" (using GIS in other modules such as field courses and in subject areas such as Environmental Monitoring and Management) (Sui, 1995). The reinforcement and consolidation achieved by teaching GIS in other modules and contexts can be especially beneficial (Brown & Olson, 2001;Kingston et al, 2012;Lo, Chang, Tu, & Yeh, 2009;Simmons, Wu, Knight, & Lopez, 2008). The extent to which in practice GIS penetrates beyond the designated module is explored further in the "Results" section.…”
mentioning
confidence: 95%
“…Geographic information systems (GIS) are increasingly being used by educators as a means to support PBL [4][5][6]. Following Simmons et al [7], GIS has the potential to enhance learning by creating a student centered inquiry environment, creating links between policy and science to help students solve real-world problems, enhancing interdisciplinary learning, enabling students to use the same tools as professionals, and being accessible to a wide range of learners.…”
Section: Introductionmentioning
confidence: 99%